Mobile-Assisted Language Learning (MALL) in Indonesian Islamic Higher Education - Yudhiantara, Rully Agung; Saehu, Andang (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
Mobile phone use has been studied in its connection with foreign language learning by many researchers concerned in Mobile Assisted language learning (MALL) for more than a decade. In Indonesian Islamic higher education context, the issues of MALL has not been discussed extensively. To respond to this need, this study was aimed at investigating the following research question: 1) How do students use their mobile phone to learn English Monolingual Dictionary (EMD) application?; 2)How do students use their mobile phone to support English language learning?. This study employed the qualitative method using case study. To collect data, this study applied observation to find out students’ engagement in using the mobile phone for learning EMD application. Students participated in this study were 40 students. Findings showed that students were able to use the mobile phone to use EMD application in English language learning (ELL). They demonstrated skill in operating EMD application which was realized in their knowledge concerning, pronunciation, grammar and meaning information when searching a particular word. In addition, there were many features that students seized from the mobile phone for English language learning. They used audio feature to operate EMD from mobile phone to boost listening skill. Their mobile phone facilitated them to record video project presenting their vocabulary learning. These activities could be done by their mobile phone existence as an introductory effort toward MALL implementation in ELL in Islamic Higher education.